A intencionalidade formativa expressa nos projetos pedagógicos das escolas rurais de ensino fundamental completo da cidade de Pelotas/RS: um estudo fundamentado na concepção marxiana de emancipação - Jardim, Lisandra Ferreira (2011)
The work aims to investigate the formative intention expressed in the Pedagogical Projects of the Municipal Schools that have the complete Elementary School in the rural area in the city of Pelotas, RS, Brazil, with reference to the marxian notion of emancipation, through a documentary analysis of philosophical nature, based on the dialectic Marxian method. In the opening chapter, it starts with the presentation of the origins of the research and the importance of studying the Pedagogical Projects, aiming to explain the importance of these documents for formal education and the relevance of researching them; then it is discussed the historical and economic context of emergence of the laws that regulate the implementation of these documents, where is given a short historical resume in order to elucidate some relations between the Brazilian society, public schools and some international institutions; finally it is presented the Marxian concept of emancipation, through a careful analysis of The Jewish Question, Marx's work that addresses the subject more specifically. In the second chapter there is the historical contextualization of the period of preparation of the Marxian dialectical method and is described its systematization; are also delineated the stages of the performance of the research, under a dialectical perspective, and determined the categories of analysis. Finally, the third chapter is devoted to the synthesis. In this step is performed the reelaboration of the chaotic original vision, when it is found out that the analyzed documents have the intention of forming emancipated citizens under the standpoint of political emancipation, since their contents express intentions and principles directed to it